Symbolic Imagery of Escapism in Lana Del Rey’s Salvatore: A Semiotic Analysis Based on Roland Barthes - Anisa Triani; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the symbolism in Lana Del Rey’s song Salvatore in order to understand how visual and lyrical imagery constructs a narrative of escapism within the context of postmodern culture. The song presents various symbols such as “soft ice cream,” “limousines,” and “summer rain” that create an aesthetic, sensual, and fantastical world detached from reality. The method used in this study is Roland Barthes’ semiotic analysis within a qualitative framework. The analysis involves identifying the denotative and connotative meanings of the key symbols in the lyrics, followed by examining the cultural myths constructed by these symbols in relation to escapism and feminine representation in popular culture. The results show that the symbols in Salvatore serve not only as representations of beauty or luxury but also as tools through which the narrator constructs an illusory escape. The symbol of “soft ice cream” signifies femininity that is soft yet commodified; “limousines” reflects false luxury under visual capitalism; while “summer rain” evokes emotional ambiguity. Thus, the song illustrates a construction of artificial reality, where escapism becomes a mode of feminine existence within a world dominated by imagery and simulation.